New Directions for the Electronic Voting Machine Ecosystem - Monteiro, José; Guimarães, Lucas; Lima, Saulo; Amorim, Marcus; Coimbra, Rodrigo (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
The embedded systems of Brazilian Electronic Voting machines (UE) and the infrastructure for pooling systems (UE Ecosystem) evolves for the inclusion of new tecnological and security advancements. In this paper we show the topics to be incorporated to the UE Ecosystem in next years.